Nanotargeted Radionuclides for Cancer Nuclear Imaging and Internal Radiotherapy. (3rd August 2010) - Ting, Gann; Chang, Chih-Hsien; Wang, Hsin-Ell; Lee, Te-Wei
Abstract : Current progress in nanomedicine has exploited the possibility of designing tumor-targeted nanocarriers being able to deliver radionuclide payloads in a site or molecular selective manner to improve the efficacy and safety of cancer imaging and therapy. Radionuclides of auger electron-, α -, β -, and γ -radiation emitters have been surface-bioconjugated or after-loaded in nanoparticles to improve the efficacy and reduce the toxicity of cancer imaging and therapy in preclinical and clinical studies. This article provides a brief overview of current status of applications, advantages, problems, up-to-date research and development, and future prospects of nanotargeted radionuclides in cancer nuclear imaging and radiotherapy. Passive and active nanotargeting delivery of radionuclides with illustrating examples for tumor imaging and therapy are reviewed and summarized. Research on combing different modes of selective delivery of radionuclides through nanocarriers targeted delivery for tumor imaging and therapy offers the new possibility of large increases in cancer diagnostic efficacy and therapeutic index. However, further efforts and challenges in preclinical and clinical efficacy and toxicity studies are required to translate those advanced technologies to the clinical applications for cancer patients.